2013
DOI: 10.5402/2013/526163
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Perioperative Oxygen (80% FIO2) for the Prevention of Surgical Site Infection after Emergency Cesarean Section

Abstract: Objective. Cesarean section can be a lifesaving procedure. However, as with many surgeries, it is not exempt of complications. Surgical site infections generate higher costs, serious morbidity, and mortality. This study evaluates the benefits of perioperative oxygen to prevent surgical site infections. Methods. We conducted a randomized controlled trial to assess the effects of perioperative oxygen to prevent surgical site infection after emergency cesarean section. Patients were randomized to receive either o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Considering patients operated under loco-regional anaesthesia, the results are more homogenous as the 6 available studies included caesarean sections and did not report any difference in the incidence of SSI between the high and low FiO2 groups. This is confirmed in the meta-analysis by de Jonge et al [91] that included 5 of the 6 studies we identified in this review with the exception of Admadé's study [70]. Thus, routine administration of supplemental oxygen to patients having caesarean section under epidural or spinal anaesthesia could be strongly questioned, considering that it does not appear to impact neither maternal nor foetal prognosis [94].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Considering patients operated under loco-regional anaesthesia, the results are more homogenous as the 6 available studies included caesarean sections and did not report any difference in the incidence of SSI between the high and low FiO2 groups. This is confirmed in the meta-analysis by de Jonge et al [91] that included 5 of the 6 studies we identified in this review with the exception of Admadé's study [70]. Thus, routine administration of supplemental oxygen to patients having caesarean section under epidural or spinal anaesthesia could be strongly questioned, considering that it does not appear to impact neither maternal nor foetal prognosis [94].…”
Section: Discussionmentioning
confidence: 55%
“…Six RCTs compared the incidence of SSI when administrating high or low FIO2 during caesarean section. Three studies had used different oxygen delivery devices between the high (concentration mask) and low (nasal cannula) FiO2 groups [69][70][71]. Only 2 studies specified the timing of antibiotic prophylaxis (at the time of cord clamping) [72,73].…”
Section: Results Of the Studies Performed During Loco-regional Anaest...mentioning
confidence: 99%
“…Eventually, 30 randomized studies were included in this meta-analysis for a total of 18,055 patients, among which 24 compared high vs. low intraoperative FiO 2 during general anesthesia (n = 15,871 patients) 19 42 and 6 during regional anesthesia (n = 2184 patients) 43 – 48 . High FiO 2 was 80% in all studies except in Park’s study (FiO 2 60%) 37 ; and low FiO 2 was 30% in all studies except in Lin’s study (FiO 2 40%) 38 , Pryor’s and Park’s studies (FiO 2 35%) 20 , 37 , Mayank’s study (FiO 2 33%) 33 , and Admadé’s study (room air) 45 .…”
Section: Resultsmentioning
confidence: 76%
“…SSI were diagnosed using the CDC definition 21 , 24 , 26 29 , 31 33 , 35 , 36 , 39 , 41 , 42 , 46 , 47 , ASEPSIS definition 25 , 30 , 34 , 48 , or other trial-specific definitions 19 , 20 , 22 , 23 , 37 , 38 , 40 , 43 45 , in respectively 16, 4 and 10 out of the 30 included studies. Confounding factors influencing the incidence of SSI were variously considered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation